RISK MANAGEMENT PRACTICES AND FINANCIAL PERFORMANCE OF SMALL AND MEDIUM SCALE AGRICULTURAL VALUE CHAIN IN KWARA STATE, NIGERIA. - Ganiyu Deji ABDULRAHEEM; Ahmed Oluwatobi ADEKUNLE (Malete Journal of Accounting and Finance, 2025)
The role of risk management practices in agricultural value chains has generated increasing attention, especially in developing economies like Nigeria. Sequel to this, this study aimed at examining the effect of risk management practices on financial performance of small and medium scale agricultural value chain in Kwara State, Nigeria. Data for the analysis was collected through field surveys filled out by SMEs in the agricultural value chain in Kwara state, with responses gathered from key decision-makers and managers. The study utilized logistic regression for the models. The empirical findings indicated that financial risk management practices and operational risk management practices were significant determinants of the financial performance of SMEs agricultural value chain Kwara State. These components were shown to positively impact profitability and operational sustainability. The study concludes that emerges of financial risk management practices and operational risk management practices were the key determinants of financial performance of SMEs agricultural value chain. The study therefore recommends among others that agricultural SMEs should enhance their market research capabilities to better understand consumer demands and trends, focus on improving operational efficiency through technology adoption, and more so invest in sustainable farming practices such as water and soil conservation.